PERBANDINGAN MONOTERAPI DAN POLITERAPI EPILEPSI TERHDAP KUALITAS HIDUP PASIEN EPILEPSI DI RSU MUHAMMADIYAH SITI AMINAH BUMIAYU TAHUN 2020 - Aina Ainun Nahdhiyah; Ismiyati Ismiyati; Baedi Mulyanto (Jurnal Farmasi Universitas Peradaban, 2021)
Epilepsi is a common disease, untreated seizures will increase the risk of death injury, cognitive and behavioral disorders and social loss. The purpose of this study was to determine the effect of epilepsy monotherapy and polytherapy on patients at RSUM Siti Aminah Bumiayu. Data collection using observasional analytic methods with cross-sectional design. The subject of the study condisted of 72 epilepsy patients at the neurological clinic of Siti Aminah Bumiayu Hospital obtained by accidental sampling technique starting from April to September 2020. Comparing monotherapy and polytherapy on the quality of life of epilepsy patients as measured by medication adherence using the Morisky Modication Adhrence Scales (MMAS) questionnaire. The result showed that the proportion of patients who received monotherapy was 72,2% and polytherapy was 27,8% while those who received epilepsy drugs phenytoin 56,9% and phenobarbital 15,3% as monotherapy and combination phenytoin+phenobarbital+caffein 27,8% as polytherapy. That there is no comparison of epilepsy monotherapy and polytherapy on the quality of life of patients with epilepsy, namely the p value is 0,998 and 0,999 (monotherapy) and 0,998 (polytherpy) where that p value is > 0,05